HUBUNGAN KUALITAS TIDUR TERHADAP TERJADINYA WASTING PADA ANAK USIA SEKOLAH - Jelita Hotma Asy Simanjuntak; Herlina Herlina; Bayhakki Bayhakki (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
This study aims to determine the relationship between the quality of sleep of school aged children against theoccurrence of wasting in school aged children. This study is a cross sectional study conducted in August until January2018. Samples are selected in SD Negeri 167 Pekanbaru using proportional stratify random sampling technique inwhich of 311 students of grade 4 and 5 were randomly selected using dice or lot and refers to number absent and got 89samples. Performed weight and height measurements to determine the wasting and filling questionnaires modified bythe PSQI researchers to determine the quality of sleeping school-age children. The results of the study showed that 9year old subjects were 9% 10 years old were 53.9% 11 years old were 29.2%, 12 years old were 6.7% and 13 years oldwere 1%. The subjects 42 male students and 71 female students and the most common body mass index category was79.8%, skinny as much as 15.7% and thin (4.5%). Students who have good sleep quality as 61 people (68.5%) and whohave poor sleep quality as 28 people (31.5%). The result of chi-square test showed no correlation between schoolquality of schoolchildren child to school wage at p = 1,000 (p> 0,05). Conclusion: There is no correlation betweenschool quality of schoolchild child to wasting in school age children.Keywords: school age children, sleep quality, wasting.